2002
DOI: 10.1038/sj.ejcn.1601312
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes and vitamin status of a sample of homeless people in Paris

Abstract: OBJECTIVE: To determine nutritional intake and vitamin status in a sample of homeless people who had been on the streets of Paris for more than 2 y. DESIGN: The nutritional status was evaluated by a 24 h recall questionnaire and by assay of circulating levels of vitamins A, B 1 , B 6 , B 12 , C and E. SETTING: The study was conducted in four accommodation centres of the SAMU Social of Paris (CHUSI units) from July 1999 to May 2000. SUBJECTS: A total of 329 homeless people were interviewed. Only 87 subjects, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 19 publications
5
51
1
6
Order By: Relevance
“…Studies have reported that 20 %-44 % of the homeless are underweight and suffer from wasting malnutrition. The same studies go on to describe vitamin and mineral insuffi ciency, as indicated by low blood levels or based on intakes below the recommended daily allowances [2][3][4][5][6][7][8][9][10][11][12]. Only a few studies have documented the absence of undernutrition in homeless populations.…”
mentioning
confidence: 99%
“…Studies have reported that 20 %-44 % of the homeless are underweight and suffer from wasting malnutrition. The same studies go on to describe vitamin and mineral insuffi ciency, as indicated by low blood levels or based on intakes below the recommended daily allowances [2][3][4][5][6][7][8][9][10][11][12]. Only a few studies have documented the absence of undernutrition in homeless populations.…”
mentioning
confidence: 99%
“…3.1 Survey method 3.1.1 Actual situation and activities of the food bank in the United States In the survey, 200 food banks were found to be currently active in the US according to the United States Department of Agriculture [8]. The philosophy behind each food bank establishment was examined to typify different organizations that can be considered food banks.…”
Section: Survey Of Food Banks In Japan and The United Statesmentioning
confidence: 99%
“…Japan-US comparison of food bank activities and the points for Japanese food banks to learn the activity in the United States Currently, there are 40 food banks in Japan and 200 or more in the United States [8]. There is a large population difference between the two, and in the United States, the Department of Agriculture is supporting the food bank activities by purchasing agricultural products from producers though there is no such system in Japan [2].…”
Section: Japan-us Comparison Of Food Bank Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of intake of vitamins and minerals has also been noted as an issue in other countries [12][13][14]. In order to improve the nutritional status of the homeless population, sufficient amounts of vegetables and fruits must be provided.…”
Section: Problem On Nutrition and Food Qualitymentioning
confidence: 99%